GAMBARAN KEJADIAN ARITMIA DAN KEJADIAN MORTALITAS PADA PASIEN STEMI DI RSUD ULIN BANJARMASIN - Anggraini, Putri; Wahid, Abdurahman; Diani, Noor (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2016)
Arrhythmias are disturbances in the heart rhythm become fast, slow or irregular. Arrhythmia is acomplication ofSTEMI. These arrhythmias can damage electrical conduction and cardiac cells inthe heart. The incidence of arrhythmias is 50%, which can lead to death. The objective todescribe the incidence of arrhythmias and an overview mortality in STEMI patients at theGeneral Hospital of Ulin Banjarmasin. The methods of study was using a descriptive with crosssectional design to STEMI patients. This study has been done since 4 September 2015-31December 2015 using accidental sampling technique. Instruments used ECG and observationsheet. The results of this study total incidence of arrhythmias were 11 respondents (65%), nonarrhythmia 6 respondents (35%). The incidence of mortality was two respondents (12%). 15respondents (88%), 2 female respondents (12%). It can be concluded the prevalence ofarrhythmias in patients with STEMI is high, found with sinus tachycardia and bradycardia mayresult in death.